2016
DOI: 10.17221/59/2016-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Use of eggshells as a raw material for production of calcium preparations

Abstract: The kinetics of calcium release from tablets obtained from modified eggshells in the form of calcium citrate and calcium carbonate was investigated. Calcium release showed the first-order kinetics. After 30 min of the experiment, 79.93% of calcium was released from tablets obtained from modified eggshells in the form of calcium citrate, reaching ~100% after 3 hours. For tablets produced with calcium carbonate, these values were 7 and 60%, respectively. The half-time of calcium release from tablets containing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Therefore, the need for alternative uses of eggshells seemed beneficial. Not only does eggshell calcium provide the best natural calcium source—better than that of limestone or coral sources (Lee and Oh, 2003, Ruff et al, 2012, Uraz et al, 2013)—it is also better absorbed by the body (Dolińska et al, 2016). Eggshell powder has been reported as safe for use by several European and Asian animal and human studies (Ruff et al, 2012, Uraz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the need for alternative uses of eggshells seemed beneficial. Not only does eggshell calcium provide the best natural calcium source—better than that of limestone or coral sources (Lee and Oh, 2003, Ruff et al, 2012, Uraz et al, 2013)—it is also better absorbed by the body (Dolińska et al, 2016). Eggshell powder has been reported as safe for use by several European and Asian animal and human studies (Ruff et al, 2012, Uraz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This procedure involved roasting the eggshells (for 2 h at 120 °C) with citric acid, followed by tableting. The synthetic calcium carbonate tablet was prepared by forming a granulate followed by drying at 60 °C for 24 h Calcium content from the calcium citrate extracted from eggshells was 100.0 ± 1.4 mg; and the amount found in the synthetic tablets 100.0 ± 2.7 mg Barbara et al 2016 …”
Section: Analysis Of the Various Methodologies Employed In Calcium Extraction From Eggshellsmentioning
confidence: 99%
“…In turn, Brun et al [35] reported that the best form of using chicken eggshells as a dietary supplement of Ca is to add them in the powdered form to, e.g., bread, pizza, and spaghetti, as it caused little changes in their texture and no changes in their taste. Calcium-enriched foods should have similar physical and sensory properties to their non-enriched counterparts [13,[36][37][38].…”
Section: Determination Of Sensory Evaluationmentioning
confidence: 99%